Preying on the poor? Opportunities and challenges for tackling the social and environmental threats of cryptocurrencies for vulnerable and low-income communities. (February 2022) - Howson, Peter; de Vries, Alex
Abstract: The rate of adoption of some cryptocurrencies is triggering alarm from energy researchers and social scientists concerned about the industry's growing environmental and social impacts. In this paper we argue that the unsustainable trajectory of some cryptocurrencies disproportionately impacts poor and vulnerable communities where cryptocurrency producers and other actors take advantage of economic instabilities, weak regulations, and access to cheap energy and other resources. Globally, over 100 million people hold cryptocurrency, mostly as a speculative asset. The digital infrastructure behind the most popular cryptocurrency, bitcoin, currently requires as much energy as the whole of Thailand, with a carbon footprint exceeding the gold mining industry. Should bitcoin's mass adoption continue, an escalating climate crisis is inevitable, disproportionately exacerbating social and environmental challenges for communities already experiencing multiple dimensions of deprivation. In mitigating these impacts, the paper considers 4 potential regulatory pathways, including: 1) promoting voluntary private-sector commitments to using only renewable energy, 2) encouraging a system of voluntary carbon offsetting, 3) using existing financial regulations and tax frameworks, and 4) imposing national and/or international bans on cryptocurrency 'mining'. The paper argues that effective environmental regulation of cryptocurrencies is urgently required, both to reduce the threat of catastrophic climate change, and to help the world's poorest towards sustainable development. However, regulating cryptocurrency mining in any context is likely to require a combination of efforts and is unlikely to result in win-win outcomes for all.